An ivestigation of classroom behaviour of teachers and its effect upon pupil participation in the instructional process - De Silva, R.S.M. (My University, 1992)
Teacher behaviour in the classroom has been a major area of research during the last few decades. A steadily growing number of studies have been devoted to the question of how teachers function within the complex teaching - learning situation. In these studies the focus is on concrete teaching behaviours within the teaching - learning situation, not in stable traits of the teacher...